Solar enhanced oxygen evolution reaction with transition metal telluride - Singh, Harish; Higuchi-Roos, Taishi; Roncoroni, Fabrice; Prendergast, David; Nath, Manashi (Frontiers in Chemistry, 2024)
The photo-enhanced electrocatalytic method of oxygen evolution reaction (OER) shows promise for enhancing the effectiveness of clear energy generation through water splitting by using renewable and sustainable source of energy. However, despite benefits of photoelectrocatalytic (PEC) water splitting, its uses are constrained by its low efficiency as a result of charge carrier recombina-tion, a large overpotential, and sluggish reaction kinetics. Here, we illustrate that Nickel telluride (NiTe) synthesized by hydrothermal methods can function as an extremely effective photo-coupled electrochemi-cal oxygen evolution reaction (POER) catalyst. In this study, NiTe was synthesized by hydrothermal method at 145°C within just an hour of reaction time. In dark conditions, the NiTe deposited on carbon cloth substrate shows a small OER overpotential (261 mV) at a current density of 10 mA cm–2, a reduced Tafel slope (65.4 mV dec–1), and negligible activity decay after 12 hr of chronoamperometry. By virtue of its enhanced photo response, excellent light harvesting ability, and increased interfacial kinetics of charge separation, the NiTe electrode under simulated solar illumination displays exceptional photoelectrochemi-cal performance exhibiting overpotential of 165 mV at current density of 10 mA cm-2, which is about 96 mV less than on dark conditions. In addition, Density function theory (DFT) investigations have been car-ried out on the NiTe surface, the results of which demonstrated a greater adsorption energy for intermedi-ate -OH adsorption on the catalyst site. Since the -OH adsorption on the catalyst site correlates to catalyst activation, it indicates the facile electrocatalytic activity of NiTe owing to favorable catalyst activation. DFT calculations also revealed the facile charge density redistribution following intermediate -OH adsorp-tion on the NiTe surface. This work demonstrates that arrays of NiTe elongated nanostructure are a promising option for both electrochemical and PEC water oxidation and offers broad suggestions for developing effective PEC devices.